Managing our natural resources - Camp, William G. (Delmar Cengage Learning, 2009)
Managing Our Natural Resources, fifth edition, was designed and written with people and the environment in which we live in mind. The original book was written specifically to meet the need for an up-to-date introductory level natural resources text for high school and postsecondary agricultural education students. It provides an overview of a wide array of topics in the broad area of natural resources management